The Effectiveness of Tax Reform on Taxpayer Compliance in Digital Age - Wijayanti, Adelia; Aditya, Dimas; Hilman, Yusuf Adam (Civiliza Publishing, 2025)
The rapid advancement of information technology has driven structural transformation in public administration systems, including the taxation sector. In response, the Indonesian government has initiated digital-based tax reform as a strategic effort to improve administrative efficiency, transparency, and accountability, while simultaneously expanding the national tax base. This study aims to evaluate the effectiveness of such digital tax reform in enhancing taxpayer compliance in the digital era, employing a qualitative approach through an extensive review of academic literature and recent policy documents. The findings indicate that the implementation of systems such as e-Filing, e-Billing, e-SPT, and the Core Tax Administration System has positively contributed to simplifying reporting and payment procedures, while also strengthening real-time oversight and control mechanisms. The study underscores the necessity of a multidimensional approach to digital tax policy development—one that not only prioritizes technological innovation but also encompasses institutional capacity-building, public education, regulatory harmonization, and the creation of an inclusive, responsive taxation system that aligns with the evolving characteristics of the digital economy. The effectiveness of tax reform depends largely on an integrated policy ecosystem and the active participation of citizens as central actors within the tax system. Therefore, Indonesia’s digital tax transformation must not only aim to increase revenue collection but also to reinforce fiscal legitimacy and long-term equity